Agama dan Pluralisme: Perspektif R.A. Kartini - Ida Rosyidah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2007)
The name R.A. Kartini (1879-1904) is familiar to us through her role in advocating for gender equality in education. In addition to gender issues, Kartini, in her letters, also expressed her personal views on socialism, capitalism, and Islam. This article attempts to examine Kartini's ideas in other fields that are rarely discussed, namely her thoughts on religion and pluralism, including her views and criticisms of Islam.